2009
DOI: 10.1002/ldr.910
|View full text |Cite
|
Sign up to set email alerts
|

Is rural migration a threat to environmental sustainability in Southern Burkina Faso?

Abstract: There is growing evidence that population pressure on the land has become the most intractable problem in the developing countries where demand for food exceeds the food production capacity of the land. Southern Burkina Faso has experienced rapid population growth, mostly driven by immigration of farmers. This study was carried out in Sissili Province and used satellite images acquired over 31-year period, census and survey data to capture migration patterns and its impacts on land use change. Results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 24 publications
7
83
0
2
Order By: Relevance
“…For Parkia biglobosa and Vitellaria paradoxa, which grow through farmer-managed natural regeneration (FMNR), population increase resulting in land scarcity was identified as a driver of forest degradation. Two studies in Southern Burkina Faso identified similar causes for the decline of dry forests and degradation in Southern Burkina Faso [6,10].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…For Parkia biglobosa and Vitellaria paradoxa, which grow through farmer-managed natural regeneration (FMNR), population increase resulting in land scarcity was identified as a driver of forest degradation. Two studies in Southern Burkina Faso identified similar causes for the decline of dry forests and degradation in Southern Burkina Faso [6,10].…”
Section: Discussionmentioning
confidence: 90%
“…Cotton cultivation is a common feature of the farming system in addition to livestock herding such as cattle, donkey, sheep and goats. The farm size varies amongst individual farmers ranging from 1 to10 ha [7,10]. The flora is dominated by perennial grass such as Andropogon gayanus Kunth, A. ascinodis C.B.…”
Section: Study Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Southern Burkina Faso has experienced a rapid population increase since the 1980s resulting from a positive natural growth and more importantly from a large immigration of farmers from drought-affected areas of the northern and central regions of the country [19][20][21][22]. Prior to immigration, the southern provinces, namely Sissili, Ziro and Nahouri, were less populated and were naturally endowed with a significant stock of dry forest [23].…”
Section: Introductionmentioning
confidence: 99%